PENGEMBALIAN KERUGIAN NEGARA DALAM AUDIT INVESTIGATIF DAN AUDIT PENGHITUNGAN KERUGIAN KEUANGAN NEGARA KAJIAN DARI SUDUT PANDANG AUDITOR PADA PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PROVINSI SULAWESI UTARA - Rochxy, Rochxy; Kalangi, Lintje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2021)
This study aims to analyze the Return on State Losses in Investigative Audits and Audits of Calculation of State Financial Losses. The Study From the Auditor's Point of View at the Representative of Indonesia's National Government Internal Auditor of North Sulawesi Province. This study uses a qualitative method with an exploratory approach. Data was obtained by in-depth interview technique. Key informants were determined by purposive sampling with the condition that they met the established criteria to obtain precise and accurate information. The results of the interviews were processed into data transcripts, then analyzed, coded, and categorized into themes. Data analysis using content analysis. The results of the study show that: (1) the return of state financial losses in investigative audits or audits of calculating state financial losses is not a common practice in carrying out audit tasks by auditors; (2) the cause of the return of state financial losses in investigative audits and audits of calculating state financial losses, namely the existence of good faith or regret from related parties, the expectation from related parties that the return of state financial losses carried out can eliminate or reduce the amount of state financial losses, and there is hope that the criminal sanction can be abolished or lighten the sentence; (3) there is no provision that prohibits the return of state financial losses before the issuance of investigative audit reports and audits of calculating state financial losses, but in practice auditors and law enforcement officers continue to adhere to the provisions of Article 4 of Law Number 31 of 1999 concerning Pemberantasan Tindak Pidana Korupsi ; (4) the return of state financial losses in the investigative audit does not affect the auditor's conclusions and does not eliminate or reduce the value of state financial losses that occur; (5) the return of state financial losses in the audit of the calculation of state financial losses does not affect the audit process and the results of the auditor's calculations.